Glucagon-Like Peptide 1 Receptor Agonists (GLP1RA) and Sodium-glucose co-transporter-2 inhibitors (SGLT2i): Making a pragmatic choice in diabetes management - Sanjay Kalra; Saptarshi Bhattacharya; Nitin Kapoor (Journal of the Pakistan Medical Association, 2022)
created opportunities for comprehensive diabetes care. Two classes of drugs, GLP1RA (glucagon-like peptide 1 receptor agonists), and SGLT2i (sodium glucose cotransporter 2 inhibitors) have demonstrated their efficacy in glucose control as well as cardiovascular risk reduction. While both can be used together, there is an ongoing debate regarding their relative advantages and limitations. We present a clinical perspective to compare and control these two classes of drugs, and promote rational prescription in diabetes praxis. Keywords: Canagliflozin, CV risk reduction, dapagliflozin, dulaglutide, empagliflozin, GLP1RA, liraglutide, obesity, semaglutide, SGLT2i.